Digital Hate and Ideology: Critical Discourse Analysis on Cyberbullying against Putri Padang - Hana Olivia Marpaung; Yessi Sherly Abigail Ambarita; Alya Saqinah; Dian Marisha Putri (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study delves into the linguistic and ideological dimensions of cyberbullying discourse directed at TikTok creator Putri Padang within the framework of Critical Discourse Analysis (CDA). In Indonesia’s digital landscape, TikTok has become one of the prominent platform for self-expression and cultural performance, yet it also serves as a site for public shaming and moral policing. Drawing on Fairclough’s (1995) three-dimensional model, this qualitative research analyzes fifty hate comments collected from several TikTok videos featuring Putri Padang to uncover how language reproduces power relations and cultural ideologies. The findings reveal that hate comments are not random acts of aggression but structured discursive practices characterized by repetition, labeling, and moral judgment. Linguistic strategies such as mockery, objectification, and intertextual humor—exemplified by terms like “muka kotak” and “Adudu”—function as mechanisms of symbolic domination, reinforcing gendered and regional hierarchies. Moreover, the comments often invoke patriarchal values and cultural authenticity to moral criticism, positioning the target as a violator of feminine and cultural norms. The research contributes to cyber-discourse studies by extending into multimodal contexts and emphasizing the need for culturally grounded approaches to online gender-based violence.